Hydrothermal dolomites in SW Sardinia (Italy): evidence for a widespread late-Variscan fluid flow event - Boni, Maria; Bechstädt, Thilo (Sedimentary geology, 2000)
Epigenetic replacive and saddle dolomite, frequently forming zebra structures (Geodic dolomite), affected Cambrian limestones and early diagenetic dolomites across large areas of the Iglesiente-Sulcis mining district (SW Sardinia, Italy). The dolomite crops out in an area of more than 500km2 and reaches a thickness of up to 600m (or even more). This rock represents one of the most extensive dolomites of epigenetic origin yet documented. Prior to dolomitization, the Cambrian carbonates underwent ductile deformation and greenschist facies metamorphism. The same is true for the overlying tectonic nappes. Fluid inclusion analysis combined with O- and Sr-isotope data indicate that the dolomitizing fluid can be categorized as a “basinal brine”. The spread in homogenization temperatures shows a gradient with values decreasing from east to west. The higher temperatures (mean of around 100°C) have been measured in eastern parts of the Iglesiente area, whereas the lowermost temperatures (mean of about 85°C) have been found along the western coast of Iglesiente. This fluid certainly can neither have come directly from the low-grade metamorphic lithotypes undergoing dolomitization, nor from the low-temperature metamorphic rocks within the overlying nappes. It is assumed that a late-Variscan hydrothermal event, which coincided with extensional tectonics, set brine circulation into motion. Dolomitization may have occurred within circulation cells, which were driven by high heat flow. Fluids originated in the underlying rocks and circulated upward to affect the overlying Cambrian carbonates. An alternative model is that the dolomitization was caused by hydrothermal brines that originated within basinal areas of the Variscan orogenic pile circulating deep within the crust, and ascended in the External Zone (Iglesiente-Sulcis). Whatever the origin, these reducing saline fluids, which carried radiogenic Sr, dolomitized a large volume of Early Paleozoic rocks. The many subhorizontal open cavities within the Geodic dolomite, only partly filled with cement, might indicate fluid overpressure at the time of dolomitization.